News about Attic Black Figure footed dishes attributed to Caylus and Campana painter - Morais, Rui (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2020)
In this paper we propose to add some examples of footed dishes that we believe can be attributed to the Caylus and the Campana painters by correctly identifying misidentified pieces through closer study. Compared to other shapes, these footed dishes are much less typical. In the Beazley Archive we have been able to find only seven complete footed dishes and one fragmentary example. The examples presented herein demonstrate that these painters were responsible for the decoration of some footed dishes in a period in which the black-figure technique was gradually being replaced by the red-figure technique.